If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(-1/3)*x-3 = y // - y
(-1/3)*x-y-3 = 0
-1/3*x-y-3 = 0 // + -y-3
-1/3*x = -(-y-3) // : -1/3
x = (-(-y-3))/(-1/3)
x = -3*(y+3)
x = -3*(y+3)
| 165=g-695 | | x+y+130=0 | | y/8-26=-18 | | 6x+y=3x-2y | | 3x-3=-2(x+1)+4(2-x) | | 3x=11/6 | | 32=2y-7 | | -23=r/-11 | | w/9=13 | | 51=4x-x | | -6(p-6)=36-6p | | g(x)=4x^2+2x-12 | | q/9--34=36 | | 26q=-650 | | -8u+7=-73 | | u+307=927 | | -14+8n=-2+2(4n-6) | | -2n-4=-24 | | (8+7)+(9-2)=18 | | 6r+9=6(r+1)+3 | | v/-28=-31 | | 4x-4=4+X+3 | | 12+x=15-12x | | 10r+5=35 | | c-13.7=-10.7 | | 2(x-5)+3x=4x-3 | | -16=m/3-20 | | y+82=591 | | 3r-28=8(1+4r)+7r | | 30z=450 | | 2=m/4-1 | | Log(4)8x+log(4)4=3 |